Evidence Based Practice in Pediatric Urolithiasis - Otukesh, Hasan; Hoseini, Rozita (Journal of Pediatric Nephrology, 2013)
Nephrolithiasis is an increasing problem in children. Due to the different presentations and etiology of this disease in children compared with adults, we decided to perform an extensive search to find trials and arrange an evidence based study in this regard. Keywords: Urolithiasis; Child; Evidence-Based Practice